2015
DOI: 10.4238/2015.august.10.6
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of polymorphisms in exon7 of the NSUN7 gene among Chinese Han men with asthenospermia

Abstract: ABSTRACT. Previous studies have shown that genetic polymorphisms in exon7 of the NSUN7 gene can be used as an infertility marker in Iranian men with asthenospermia. However, there have been no equivalent studies in China. In the present study, we investigated the possible association between the genetic polymorphisms in exon7 of NSUN7 and asthenospermia in a Chinese Han population. We recruited 240 asthenospermic men as a patient group and 256 normospermic men as a control group, and analyzed the semen paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…In asthenospermic patients, the transversion mutation in exon7 of NSUN7 results in change of protein spatial structure, protein folding, and ligand binding sites, leading to infertility (Khosronezhad, Colagar, & Jorsarayi, 2015). Intriguingly, another study found that transversion mutation of exon7 was not related to asthenospermia in Chinese Han men (Ren, Zhong, Ding, Chen, & Jing, 2015). Meanwhile, NSUN7 was broadly expressed during mouse embryo development and the defect of NSUN7 might lead to male sterility and intellectual disability (Chi & Delgado‐Olguín, 2013).…”
Section: Methyltranferasesmentioning
confidence: 98%
“…In asthenospermic patients, the transversion mutation in exon7 of NSUN7 results in change of protein spatial structure, protein folding, and ligand binding sites, leading to infertility (Khosronezhad, Colagar, & Jorsarayi, 2015). Intriguingly, another study found that transversion mutation of exon7 was not related to asthenospermia in Chinese Han men (Ren, Zhong, Ding, Chen, & Jing, 2015). Meanwhile, NSUN7 was broadly expressed during mouse embryo development and the defect of NSUN7 might lead to male sterility and intellectual disability (Chi & Delgado‐Olguín, 2013).…”
Section: Methyltranferasesmentioning
confidence: 98%
“…Mouse model studies have shown that the structural integrity of the flagella is of extreme importance for normal sperm motility, and defects in the axoneme assembly render poor sperm motility 52 . Not surprisingly, WES has identified a large number of genetic variants relevant to asthenozoospermia, while each variant is likely responsible for just a small fraction of patients, particularly including ADCY10 53 , CATSPER1-4 54 , EIF4G1 55 , GALNTL5 56 , NSUN7 57 , PLA2G6 54 , SPAG17 58 , and TRPC5 59 (Table 1 ).…”
Section: Spermiogenic Defects: Insight View From Mouse Modelsmentioning
confidence: 99%
“…In humans, RNA m 5 C formation is catalysed by the tRNA aspartic acid MTase 1 (TRDMT1/DNMT2), and by seven proteins of the NOP2/Sun domain family (NSUN1-7) (Garc ıa-V ılchez et al, 2019). Pathogenic mutations in humans have been mapped to several genes involved in the m 5 C pathway (Abbasi-Moheb et al, 2012;Khan et al, 2012;Martinez et al, 2012;Khosronezhad et al, 2015;Komara et al, 2015;Ren et al, 2015;Haag et al, 2016;Nakano et al, 2016;Van Haute et al, 2016). Despite its conservation and clear relevance, the functions and molecular interactions of the RNA m 5 C methylome remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%